2015
DOI: 10.1177/1753193415596497
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the effectiveness of corticosteroid injections between trigger fingers with and without proximal interphalangeal joint flexion contracture

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…We noted a trend toward more operative trigger digit releases between 2005 and 2012. This is an interesting finding, as prior studies have demonstrated success rates between 61% and 84% for one to three corticosteroid injections in patients with new onset triggering (Clark et al, 1973;Fauno et al, 1989;Newport et al, 1990;Patel and Bassini, 1992;Shinomiya et al, 2016;Wojahn et al, 2014). The reason for this increase may be multifactorial, as patients may have better access to healthcare or are less inclined to pursue nonoperative management given the very high rate of success of trigger digit release or the number of patients seeking treatment for the condition may also have increased over the study period (Cakmak et al, 2012;Lange-Riess et al, 2009;Ryzewicz and Wolf, 2006).…”
Section: Discussionmentioning
confidence: 70%
“…We noted a trend toward more operative trigger digit releases between 2005 and 2012. This is an interesting finding, as prior studies have demonstrated success rates between 61% and 84% for one to three corticosteroid injections in patients with new onset triggering (Clark et al, 1973;Fauno et al, 1989;Newport et al, 1990;Patel and Bassini, 1992;Shinomiya et al, 2016;Wojahn et al, 2014). The reason for this increase may be multifactorial, as patients may have better access to healthcare or are less inclined to pursue nonoperative management given the very high rate of success of trigger digit release or the number of patients seeking treatment for the condition may also have increased over the study period (Cakmak et al, 2012;Lange-Riess et al, 2009;Ryzewicz and Wolf, 2006).…”
Section: Discussionmentioning
confidence: 70%
“…Patients with locking finger that was actively correctable were included in this study to ensure the precision of our results. Shinomiya et al (2016) noted that corticosteroid injection was less effective in trigger finger with proximal interphalangeal joint flexion contracture compared with those without contracture. Salim et al (2012) investigated the effectiveness of physiotherapy and corticosteroid injection in patients with mild trigger finger.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons are not impartial in their choice of treatment, and the experience of the surgeon is important when choosing treatment, as shown by the fact that fewer stage IV cases were seen in those patients who were initially treated with steroids than in those initially treated surgically. 20 Our results show that an injection is less successful in patients with stage IV than in those with a lower Quinnell stage of trigger finger. The incidence of Quinnell IV fingers was low in our study (2.1%).…”
Section: Discussionmentioning
confidence: 57%